2011
DOI: 10.1155/2011/953410
|View full text |Cite
|
Sign up to set email alerts
|

Serum Resistin Level in Obese Male Children

Abstract: Objectives. Resistin is a member of cysteine-rich molecules. Several studies have been carried out to determine the biological effect of resistin, nevertheless a significant number are animal studies. All the studies performed regarding the relationship between serum resistin and obesity were merely accomplished in women. To the best of our knowledge, there is no survey on the correlation of the serum resistin level and obesity in male children. The aim of the present study is to assess serum concentration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 20 publications
0
7
1
1
Order By: Relevance
“…1 Later studies however, documented contrary findings attributing the lower levels of resistin in obese rodents to its suppression by free fatty acids. 28 The present study showed that in Nigerian-Africans, plasma resistin levels rose with increasing BMI categories with highest levels in subjects with severe obesity, however, with no significant positive correlation with age, insulin resistance, fasting insulin, fasting blood glucose, body mass index and central obesity. This is consistent with some previous study, which showed significantly higher resistin concentrations in overweight and obese subjects but without correlation with insulin resistance, blood glucose, lipids, insulin and changes in body mass index & visceral fat except for positive correlations with age.…”
Section: Discussioncontrasting
confidence: 47%
“…1 Later studies however, documented contrary findings attributing the lower levels of resistin in obese rodents to its suppression by free fatty acids. 28 The present study showed that in Nigerian-Africans, plasma resistin levels rose with increasing BMI categories with highest levels in subjects with severe obesity, however, with no significant positive correlation with age, insulin resistance, fasting insulin, fasting blood glucose, body mass index and central obesity. This is consistent with some previous study, which showed significantly higher resistin concentrations in overweight and obese subjects but without correlation with insulin resistance, blood glucose, lipids, insulin and changes in body mass index & visceral fat except for positive correlations with age.…”
Section: Discussioncontrasting
confidence: 47%
“…However, in humans, resistin is predominantly produced by non-adipocytes such as monocytes/macrophages [27], and increased blood level in resistin is caused by secretion from macrophage-invaded adipocytes [12, 24]. Recent evidence in humans suggests that the serum resistin concentration does not reflect the degree of obesity [1, 7, 14, 21]. According to our unpublished data, feline resistin mRNA is expressed not only in adipose tissue, but also within the lung and spleen.…”
Section: Discussionmentioning
confidence: 99%
“…This was similar to the results of a study conducted in Iran. 21 Elevated levels of resistin in this study have been obtained in acanthosis nigricans scale 2. The study of Lestari R (2010) obtained a mean HOMA-IR was higher in subjects with higher debree of acanthosis nigricans, especially in the group of acanthosis nigricans scale 3 and 4.…”
Section: Discussionmentioning
confidence: 64%